EFEKTIVITAS PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT MISKIN - Gita Nanda Sulistiya; Isna Fitria Agustina (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study aims to analyze the effectiveness of the Non-Cash Food Assistance Program (BPNT) in improving the welfare of poor communities in Larangan Village, Candi Sub-district, Sidoarjo Regency. This research is important given the persistence of administrative problems and variations in the level of BPNT implementation success at the village level. The study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, field observations, and documentation of BPNT program implementation. Program effectiveness was analyzed using Duncan’s effectiveness indicators as cited in Steers, namely goal attainment, integration, and adaptation. The findings indicate that the implementation of the BPNT Program in Larangan Village is moderately effective. In terms of goal attainment, the program is well targeted, as assistance is provided to poor households that genuinely need it, particularly vulnerable groups such as elderly people without stable income. In terms of integration, coordination and socialization among the village government, hamlet heads, neighborhood (RW), and community (RT) units run well, enabling program information to be evenly disseminated to the community. Meanwhile, in terms of adaptation, beneficiaries are able to adjust to the non-cash distribution system based on electronic cards, although administrative problems such as data discrepancies and delays in fund disbursement still occur. The novelty of this study lies in the application of Duncan’s effectiveness indicators in the context of village governance and in its empirical findings regarding administrative barriers that directly affect program effectiveness at the local level. This study provides practical implications for village governments and policymakers to strengthen data validation, enhance cross-actor coordination, and simplify administrative procedures in order to improve the effectiveness and sustainability of the BPNT Program.